Cutaneous Vasculitis and Asthenia in a Patient with HCV-Related Chronic Liver Disease without Detectable Serum Cryoglobulinemia - Ibraheem G. Hosiki, (Journal of King Abdulaziz University: Medical Sciences, 2023)
This paper reports a case of 47-year-old lady with Hepatitis C virus related chronic liver disease who presented with asthenia and purpuric skin eruption involving her lower limbs. Punched skin biopsy from one of those lesions was consistent with small vessels vasculitis. Although Hepatitis C virus-related vasculitis is usually associated with cryoglobulinemia, in the present case the serum Cryoglobulins were not detected on three different occasions. Moreover, testing for indirect biomarkers for mixed cryoglobulinemia (rheumatoid factor and low complement-4) were negative. The patient treated with PEG-interferon alfa-2a plus ribavirin for 24 weeks and showed partial virological response. However, after two months from the start of treatment the cutaneous lesion disappeared completely with marked improvement of asthenia and remained asymptomatic during a follow-up period of 12 months after the antiviral treatment stopped. This case highlights that patients with Hepatitis C virus may have cutaneous vasculitis without detectable serum Cryoglobulins. Combination therapy with PEG-interferon alfa-2a and ribavirin is an effective treatment approach for such patients